(untitled) (Global Journal of Science Frontier Research, 2015)
We propose here a new theory of the cosmic evolution of the universe, giving its name as the "oscillating theory of the universe". In this theory we have an endless universe having different epochs in its continuing endless process, an epoch being equal to one complete oscillation starting from a big bang like event and undergoing through different phases until it arrives at a pseudo crunch to be followed by another big bang like event, of course, after a bounce. This moment of time is the end of an epoch and the beginning of another new epoch, which happens after a complete oscillation. In this oscillating theory the length of an epoch need not be equal to the length of another epoch. And interestingly, it is found that there exists the significance of negative time at some point during the cosmic evolution of the universe.